Filsafat Sebagai Ilmu Dalam Praktik Bisnis dan Pembentukan Merek Dagang - Savira Andjani; Nandang Ihwanudin (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
Business philosophy is a set of principles and beliefs owned by the company or every business actor to move and navigate the company to achieve success based on moral principles, human rights and business ethics. The brand as a moral policy and and nothing is covered up ethically, socially, or politically. To cover the brand is done through IPR, as an object in the rahn agreement. In Islamic branding, the competitive elements of naffus and ta‟awun (Competition and help) are taught as islamic business philosophies.  Some of the business philosophies of a large company that are already well-known and have underlying its business map are the Google company, including: a. You can make money without committing a crime; b. It is best to do one thing very well. This philosophy, as the Google company does, may relate to Profitability, Customers, Employees, Services, and Products.